Aluminum alloy, shell and terminal equipment
By adding Zn, MG, CU, and X to aluminum alloy to form a specific structure, it solves the problem of difficulty in meeting the existing aluminum alloy at the same time to meet the problem of high elastic modulus and anode oxidation treatment. The efficiency of the shell and the excellent anode appearance effect.
Patent Information
- Application Number
- CN202310883188.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2025-01-21
AI Technical Summary
Existing aluminum alloys are difficult to meet the effects of high elastic modulus and anodizing treatment at the same time, and cannot be applied to the housing of thin and light terminal equipment.
By adding Zn, MG, CU, and X elements (NI, B or Li) to aluminum alloy, MGZN2 phase, ALX phase and AlxCu phase are formed, which improves the elastic modulus of aluminum alloy and is completely dissolved in the anode oxidation process. Affect the anode appearance effect.
The high elastic modulus of aluminum alloy and the effect of anode oxidation treatment are available, which is suitable for the shell of the thin and light terminal equipment, and provides excellent anode appearance and strong toughness.
Smart Images

Figure BDA0004347565720000051 
Figure BDA0004347565720000061 
Figure BDA0004347565720000081
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of aluminum alloys, and in particular to an aluminum alloy, a housing, and a terminal device. Background Art
[0002] Thin and light terminal devices are gradually being widely used. To support the continuous thinning of terminal devices, the shell of the terminal device needs to use a material with a high elastic modulus, and the shell of the terminal device also needs to have an anodized appearance. At present, the existing aluminum alloys are difficult to meet the requirements of high elastic modulus and anodization treatment at the same time, and thus cannot be used in terminal devices. Summary of the invention
[0003] The purpose of the embodiments of the present application is to provide an aluminum alloy, a shell and a terminal device. The aluminum alloy has a high elastic modulus and can be anodized. The shell formed by using the aluminum alloy has a good anode appearance effect and can be applied to terminal equipment.
[0004] An embodiment of the present application provides an aluminum alloy, and the components of the aluminum alloy include, based on the mass of the aluminum alloy: 4.0%≤Zn≤7.0%, 1.0%≤Mg≤3.0%, 0.1%≤Cu≤4.0%, 0<Mn≤0.8%, 0≤X<6%, 78.2%≤Al≤94.9%, and the total content of unavoidable impurity elements ≤1.0%, wherein the X element is selected from at least one of Ni element, B element, and Li element.
[0005] In the aluminum alloy provided in the embodiment of the present application, by adopting the aluminum alloy formula, on the one hand, the aluminum alloy can be made to have the effect of anodizing treatment, so that the shell made of the aluminum alloy has a better anode appearance effect, and on the other hand, the elastic modulus of the aluminum alloy can be greatly improved, thereby facilitating the improvement of the elastic modulus of the shell made of the aluminum alloy. Specifically, the added Zn element and Mg element are the main strengthening elements, and the Zn element and the Mg element mainly form the MgZn2 phase. The solubility of MgZn2 at the eutectic temperature of 470°C is 28%, and the solubility decreases rapidly when the temperature decreases, so it has a significant aging strengthening effect. The aluminum alloy provided in the embodiment of the present application can significantly improve the elastic modulus of the aluminum alloy by increasing the Zn element content and the Mg element content within the solid solubility limit of MgZn2. In addition, by adding the X element, the X element can generate a high modulus AlX phase with the Al element in situ, thereby facilitating the further improvement of the elastic modulus of the aluminum alloy, and the high modulus AlX phase can be completely dissolved during the anodization process of the aluminum alloy, without affecting the anode appearance effect of the aluminum alloy. By adding Cu to the aluminum alloy, Cu can generate an anode-soluble high modulus AlXCu phase with a high modulus AlX phase, which is conducive to further improving the elastic modulus of the aluminum alloy. In addition, the Cu content in the aluminum alloy is relatively high. On the one hand, it can significantly improve the elastic modulus of the aluminum alloy by increasing the proportion of the high modulus AlXCu phase. On the other hand, Cu can accelerate the aging of the aluminum alloy to improve the elastic modulus of the aluminum alloy and improve the quenching sensitivity of the aluminum alloy. At the same time, the CuMgAl2 formed by the Cu element, the Mg element and the Al element can be the core of the aging strengthening phase, so that the Guinier Preston zone (GP zone) is accelerated to become an intermediate phase, accelerating the early aging process, thereby helping to improve the elastic modulus of the aluminum alloy. The Mn element added to the aluminum alloy can hinder the growth process of the nucleation of the recrystallization of the aluminum alloy, has a certain strengthening effect on the aluminum alloy, and can also improve the yield strength, tensile strength and elongation of the aluminum alloy, thereby helping the aluminum alloy to present a strong toughness and reduce the sensitivity to stress corrosion cracking.
[0006] In a possible implementation, X is Ni, and the mass ratio of Cu to Ni is: Cu:Ni=(0.5-2.0):(1.0-2.0). Within this mass ratio range of components, the aluminum alloy can obtain an excellent elastic modulus, as well as good yield strength, tensile strength and elongation, so that the aluminum alloy exhibits toughness and can obtain a bright anode appearance.
[0007] In a possible implementation, X is element B, and the mass ratio of Cu to element B is: Cu:B=(0.5-2.0):(1.0-2.0). Within this composition mass ratio range, the aluminum alloy can obtain an excellent elastic modulus, as well as good yield strength, tensile strength and elongation, so that the aluminum alloy exhibits strong toughness and can obtain a bright anode appearance.
[0008] In a possible implementation, X is Li element, and the mass ratio of Cu to Li element is: Cu:Li=(0.5-2.0):(1.0-2.0). Within this composition mass ratio range, the aluminum alloy can obtain an excellent elastic modulus, as well as good yield strength, tensile strength and elongation, so that the aluminum alloy exhibits strong toughness and can obtain a bright anode appearance.
[0009] In a possible implementation, X is Ni, B and Li, and the mass ratio of Cu to Ni, B and Ni is: Cu: Ni: B: Li = (0.5-2.0): (0.6-1.2): (0.2-0.4): (0.4-0.7). Within this mass ratio range of components, the aluminum alloy can obtain an excellent elastic modulus, as well as good yield strength, tensile strength and elongation, so that the aluminum alloy exhibits toughness and can obtain a bright anode appearance.
[0010] In a possible implementation, the aluminum alloy includes an Al matrix and second phase particles dispersed in the Al matrix, the Al matrix is formed of Al element, and the second phase particles are formed of at least two elements selected from the group consisting of Al element, Mg element, Zn element, Cu element, Mn element and X element.
[0011] In a possible embodiment, in the cross section of the aluminum alloy, within 0.05 mm 2 In the cross-sectional area, the number of second-phase particles with a diameter of ≥8μm is ≤30. If the size of the second-phase particles is too large or the number is too large, the second-phase particles will not be completely dissolved during anodization, resulting in the appearance of the aluminum alloy anode being numb and dull. By controlling the cross-sectional area of the aluminum alloy, within 0.05mm 2 Within the cross-sectional area, the number of second phase particles with a diameter of ≥8 μm is ≤30, so as to ensure that the aluminum alloy has a better high-brightness anode appearance effect.
[0012] In a possible implementation manner, the unavoidable impurity elements include at least one of Ti, Cr, and Fe.
[0013] In a possible implementation, 0.2%≤Cu≤3.0%, 1.0%≤X≤5.5%. In this composition range, the aluminum alloy can obtain excellent elastic modulus, as well as good yield strength, tensile strength and elongation, so that the aluminum alloy exhibits strong toughness.
[0014] In a possible implementation, 0.5% ≤ Cu ≤ 2.0%, 1.0% ≤ X ≤ 2.0%. In this composition range, the aluminum alloy can obtain excellent elastic modulus, as well as good yield strength, tensile strength and elongation, so that the aluminum alloy exhibits strong toughness and can obtain a bright anode appearance.
[0015] The embodiment of the present application also provides a shell, which is made of the above-mentioned aluminum alloy.
[0016] An embodiment of the present application also provides a terminal device, including a display screen and a shell as described above, wherein the display screen is mounted on the shell.
[0017] In a possible implementation, the terminal device is a mobile phone, and the shell is the middle frame of the mobile phone; or, the terminal device is a tablet computer, and the shell is the middle frame of the tablet computer; or, the terminal device is a computer, and the shell is the shell of the computer. DETAILED DESCRIPTION
[0018] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0019] Anodic oxidation: refers to a material protection technology in which an oxide film is formed on the surface of a metal material by applying an external anodic current in an electrolyte solution; for example, an aluminum alloy is placed in an electrolyte solution and an external anodic current is applied to form an oxide film on the surface of the aluminum alloy.
[0020] The embodiment of the present application provides a terminal device, the terminal device includes a display screen and a housing, and the display screen is mounted on the housing. The terminal device may be a mobile phone, a tablet computer, a computer, a wearable product, or other device. Exemplarily, the terminal device is a mobile phone, in which case the housing may be the middle frame of the mobile phone. The terminal device is a tablet computer, in which case the housing may be the middle frame of the tablet computer. The terminal device is a computer (Personal Computer, PC), in which case the housing may be the housing of the computer (PC housing).
[0021] The shell can be made by aluminum alloy processing. In one embodiment of the present application, an aluminum alloy is provided. The composition of the aluminum alloy includes, by weight of the aluminum alloy, 4.0%≤Zn≤6.5%, 1.0%≤Mg≤2.8%, 0.1%≤Cu≤4.5%, 0<Mn≤0.6%, 0≤X<6%, 78.2%≤Al≤94.9%, and the total content of inevitable impurity elements is ≤1.0%, wherein the X element is selected from at least one of the B element, the Li element, and the Ni element.
[0022] Exemplarily, based on the mass of the aluminum alloy, the content of the Zn element in the aluminum alloy may be 4.0%, 5.5%, 6.5%, and any values between the above values. Based on the mass of the aluminum alloy, the content of the Mg element in the aluminum alloy may be 1.0%, 2.0%, 2.8%, and any values between the above values. Based on the mass of the aluminum alloy, the content of the Cu element in the aluminum alloy may be 0.1%, 0.5%, 1.5%, 2.0%, 4.5%, and any values between the above values. Based on the mass of the aluminum alloy, the content of the Mn element in the aluminum alloy may be 0.1%, 0.2%, 0.6%, and any values between the above values. Based on the mass of the aluminum alloy, the content of the X element in the aluminum alloy can be 0%, 0.2%, 0.4%, 0.6%, 1.0%, 1.2%, 2.0%, 2.3%, 4.0%, 5.9%, etc., and any values between the above values. Based on the mass of the aluminum alloy, the content of the Al element in the aluminum alloy can be 78.2%, 85.54%, 87.55%, 89.57%, 91.54%, 94.72%, 94.9%, etc., and any values between the above values.
[0023] The elastic modulus of existing aluminum alloys is generally 68 to 70 GPa, while in the aluminum alloys of the embodiments of the present application, the added Zn and Mg elements are the main strengthening elements, and the Zn and Mg elements mainly form the MgZn2 phase. The solubility of MgZn2 at the eutectic temperature of 470°C is 28%, and the solubility decreases rapidly when the temperature decreases, so it has a significant aging strengthening effect. The aluminum alloy provided in the embodiments of the present application can significantly improve the elastic modulus of the aluminum alloy by increasing the Zn and Mg content within the solid solubility limit of MgZn2.
[0024] In addition, by adding X element, X element can generate high modulus AlX phase with Al element in situ, which is conducive to further improving the elastic modulus of aluminum alloy, and the high modulus AlX phase can be completely dissolved during the aluminum alloy anodization process, without affecting the anode appearance of aluminum alloy. By adding Cu to the aluminum alloy, Cu can generate anode soluble high modulus AlXCu phase with high modulus AlX phase, which is conducive to further improving the elastic modulus of aluminum alloy.
[0025] In addition, the high Cu content in aluminum alloy can significantly improve the elastic modulus of aluminum alloy by increasing the proportion of high modulus AlXCu phase on the one hand, and on the other hand, Cu can accelerate the aging of aluminum alloy to improve the elastic modulus of aluminum alloy and improve the quenching sensitivity of aluminum alloy. At the same time, CuMgAl2 formed by Cu, Mg and Al elements can be the core of the aging strengthening phase, accelerating the Guinier Preston (GP) zone to become an intermediate phase, accelerating the early aging process, and thus improving the elastic modulus of aluminum alloy. The Mn element added to the aluminum alloy can hinder the nucleation and growth process of the recrystallization of the aluminum alloy, have a certain strengthening effect on the aluminum alloy, and can also improve the yield strength, tensile strength and elongation of the aluminum alloy, thereby helping the aluminum alloy to present a strong toughness and reduce the sensitivity to stress corrosion cracking.
[0026] In the aluminum alloy formula provided in the embodiment of the present application, by adopting this aluminum alloy formula, on the one hand, the aluminum alloy can have the effect of being anodized, so that the shell made of the aluminum alloy has a better anode appearance effect, and on the other hand, it can also greatly improve the elastic modulus of the aluminum alloy, thereby facilitating improving the elastic modulus of the shell made of the aluminum alloy.
[0027] Among them, in some possible implementations, the aluminum alloy can be further controlled to have 0.2% ≤ Cu ≤ 3.0%, and 1.0% ≤ X ≤ 5.5%. Under this composition range, the aluminum alloy can obtain excellent elastic modulus, as well as good yield strength, tensile strength and elongation, so that the aluminum alloy exhibits strong toughness.
[0028] In some possible implementations, the aluminum alloy can be further controlled to have 0.5% ≤ Cu ≤ 2.0% and 1.0% ≤ X ≤ 2.0%. Under this composition range, the aluminum alloy can obtain an excellent elastic modulus, as well as good yield strength, tensile strength and elongation, so that the aluminum alloy exhibits strong toughness and can obtain a bright anode appearance.
[0029] In addition, in some possible implementations, in the aluminum alloy, X is Ni element, and the mass ratio of Cu to Ni element is controlled to be: Cu: Ni = (0.5-2.0): (1.0-2.0). Under this composition mass ratio range, the aluminum alloy can obtain excellent elastic modulus, as well as good yield strength, tensile strength and elongation, so that the aluminum alloy exhibits strong toughness and can obtain a bright anode appearance effect.
[0030] In some possible implementations, in the aluminum alloy, X is the B element, and the mass ratio of Cu to B is controlled to be: Cu:B=(0.5-2.0):(1.0-2.0). Within this composition mass ratio range, the aluminum alloy can obtain an excellent elastic modulus, as well as good yield strength, tensile strength and elongation, so that the aluminum alloy exhibits strong toughness and can obtain a bright anode appearance.
[0031] In some possible implementations, in the aluminum alloy, X is the Li element, and the mass ratio of Cu to Li is controlled to be: Cu: Li = (0.5-2.0): (1.0-2.0). Within this composition mass ratio range, the aluminum alloy can obtain an excellent elastic modulus, as well as good yield strength, tensile strength and elongation, so that the aluminum alloy exhibits strong toughness and can obtain a bright anode appearance.
[0032] In some possible implementations, in the aluminum alloy, X is Ni, B and Li, and the mass ratio of Cu to Ni, B and Ni is controlled to be: Cu: Ni: B: Li = (0.5-2.0): (0.6-1.2): (0.2-0.4): (0.4-0.7). Within this composition mass ratio range, the aluminum alloy can obtain an excellent elastic modulus, as well as good yield strength, tensile strength and elongation, so that the aluminum alloy exhibits strong toughness and can obtain a good anode appearance effect.
[0033] In some possible implementations, the aluminum alloy includes an Al matrix and second-phase particles dispersed in the Al matrix, the Al matrix is formed of Al element, and the second-phase particles are formed of at least two elements selected from the group consisting of Al element, Mg element, Zn element, Cu element, Mn element, and X element. For example, the second-phase particles may be Al 12 Mg 17The second phase particles may be Al-Ni particles, MgZn2 particles, ternary particles formed by Al-Cu-Mg, or particles doped with Mn element in the above particles. Exemplarily, when the X element is Ni element, the second phase particles may be Al-Ni particles. When the X element is B element, the second phase particles may be Al-B particles. When the X element is Li element, the second phase particles may be Al-Li particles. When the X element is Ni element, B element and Li element, the second phase particles may be Al-Ni particles, Al-B particles and Al-Li particles.
[0034] If the size of the second phase particles is too large or the number is too large, the second phase particles will not be completely dissolved during anodization, resulting in a numb and dull appearance of the aluminum alloy anode. In some possible implementations, in the cross section of the aluminum alloy, within 0.05 mm 2 Within the cross-sectional area, the number of second phase particles with a diameter of ≥8 μm is ≤30, so as to ensure that the aluminum alloy has a better high-brightness anode appearance effect.
[0035] The present application also provides a method for preparing the aluminum alloy, comprising:
[0036] S1. Take the raw materials of aluminum alloy according to the composition of aluminum alloy, melt and cast to obtain ingots. Exemplarily, the aluminum alloy raw material corresponding to the Zn element in the aluminum alloy is Al-Zn master alloy, the aluminum alloy raw material corresponding to the Mg element is Al-Mg master alloy, the aluminum alloy raw material corresponding to the Cu element is Al-Cu master alloy, the aluminum alloy raw material corresponding to the Mn element is Al-Mn master alloy, the aluminum alloy raw material mainly corresponding to the Al element is pure Al ingot, the aluminum alloy raw material corresponding to the Ni element is Al-Ni master alloy, the aluminum alloy raw material corresponding to the B element is Al-B master alloy, and the aluminum alloy raw material corresponding to the Li element is Al-Li master alloy.
[0037] S2. subjecting the ingot to homogenization annealing treatment.
[0038] S3, extruding the ingot that has been subjected to homogenization annealing treatment to obtain an extruded material.
[0039] S4. Performing aging treatment on the extruded material to obtain an aluminum alloy.
[0040] Among them, in some possible implementations, step S2 is specifically: keeping the ingot at 570° C. to 620° C. for 3 h to 8 h to perform homogenization annealing treatment.
[0041] In some possible implementations, in step S3, the ingot subjected to homogenization annealing is extruded at an ingot temperature of 520°C to 570°C, an extrusion speed of 5m / min to 10m / min, and an outlet temperature of 530°C to 560°C to obtain an extruded material.
[0042] In some possible implementations, in step S4, the extruded material is kept at 150° C. to 225° C. for 5 h to 12 h for aging treatment.
[0043] In some possible implementations, between step S3 and step S4, the following further step is included: S31, pre-deforming the extruded material.
[0044] In some possible implementations, after step S4, the method further includes: S5, performing cold deformation processing on the aluminum alloy.
[0045] Among them, both step S31 and step S5 can improve the toughness of the aluminum alloy.
[0046] The properties of the aluminum alloy provided in this application are described below in conjunction with specific embodiments.
[0047] Comparative Examples 1 to 4 and Examples 1 to 25 all provide an aluminum alloy, and the components of the aluminum alloy are shown in Table 1. Among them, the impurity elements in the aluminum alloys of Comparative Examples 1 to 4 and Examples 1 to 25 include Ti, Cr and Fe.
[0048] Table 1 Composition of aluminum alloys of Comparative Examples 1-4 and Examples 1-25
[0049]
[0050]
[0051] The aluminum alloy provided in Example 1 is prepared according to the following steps:
[0052] S1. Weighing raw materials of aluminum alloy according to the components of aluminum alloy in Table 1 and performing melting and casting to obtain an ingot;
[0053] S2, keeping the ingot at 620°C for 3h for homogenization annealing;
[0054] S3, extruding the ingot subjected to homogenization annealing at an ingot temperature of 570° C., an extrusion speed of 10 m / min, and an outlet temperature of 560° C. to obtain an extruded material;
[0055] S31, pre-deforming the extruded material;
[0056] S4, keeping the extruded material treated by S31 at 225° C. for 5 hours for aging treatment to obtain an aluminum alloy;
[0057] S5. Perform cold deformation processing on the aluminum alloy.
[0058] The raw materials of the aluminum alloy in Example 1 include Al-Zn master alloy, Al-Mg master alloy, Al-Cu master alloy, Al-Mn master alloy and pure Al ingot.
[0059] The aluminum alloy provided in Example 2 is prepared according to the following steps:
[0060] S1. Weighing raw materials of aluminum alloy according to the components of aluminum alloy in Table 1 and performing melting and casting to obtain an ingot;
[0061] S2, keeping the ingot at 600°C for 5 hours for homogenization annealing;
[0062] S3, extruding the ingot subjected to homogenization annealing treatment at an ingot temperature of 550° C., an extrusion speed of 8 m / min, and an outlet temperature of 540° C. to obtain an extruded material;
[0063] S31, pre-deforming the extruded material;
[0064] S4, keeping the extruded material treated by S31 at 175° C. for 8 hours for aging treatment to obtain an aluminum alloy;
[0065] S5. Perform cold deformation processing on the aluminum alloy.
[0066] The raw materials of the aluminum alloy in Example 2 include Al-Zn master alloy, Al-Mg master alloy, Al-Cu master alloy, Al-Mn master alloy and pure Al ingot.
[0067] The aluminum alloys provided in Examples 3-25 have the same preparation steps as those in Example 2, except that the raw materials of the aluminum alloy in Example 3 include Al-Zn master alloy, Al-Mg master alloy, Al-Cu master alloy, Al-Mn master alloy and pure Al ingot, the raw materials of the aluminum alloys in Examples 4-6 and Examples 15-17 include Al-Zn master alloy, Al-Mg master alloy, Al-Cu master alloy, Al-Mn master alloy, Al-Ni master alloy and pure Al ingot, and the raw materials of the aluminum alloys in Examples 7-9 and Examples 18-20 include Al-Zn master alloy, Al-Mg master alloy, Al-Cu intermediate alloy, Al-Mn intermediate alloy, Al-B intermediate alloy and pure Al ingot. The raw materials of the aluminum alloy in Examples 10-12 and 21-23 include Al-Zn intermediate alloy, Al-Mg intermediate alloy, Al-Cu intermediate alloy, Al-Mn intermediate alloy, Al-Li intermediate alloy and pure Al ingot. The raw materials of the aluminum alloy in Examples 13-14 and 23-25 include Al-Zn intermediate alloy, Al-Mg intermediate alloy, Al-Cu intermediate alloy, Al-Mn intermediate alloy, Al-Ni intermediate alloy, Al-B intermediate alloy, Al-Li intermediate alloy and pure Al ingot.
[0068] The aluminum alloy provided in Comparative Example 1 was prepared according to the following steps:
[0069] S1. Weighing raw materials of aluminum alloy according to the components of aluminum alloy in Table 1 and performing melting and casting to obtain an ingot;
[0070] S2, keeping the ingot at 570°C for 8h for homogenization annealing;
[0071] S3, extruding the ingot subjected to homogenization annealing at an ingot temperature of 520° C., an extrusion speed of 5 m / min, and an outlet temperature of 510° C. to obtain an extruded material;
[0072] S31, pre-deforming the extruded material;
[0073] S4, keeping the extruded material treated by S31 at 150° C. for 12 hours for aging treatment to obtain an aluminum alloy;
[0074] S5. Perform cold deformation processing on the aluminum alloy.
[0075] Among them, the raw materials of the aluminum alloy in Comparative Example 1 include Al-Zn master alloy, Al-Mg master alloy, Al-Cu master alloy, Al-Mn master alloy and pure Al ingot.
[0076] The aluminum alloys provided in Comparative Examples 2-4 have the same preparation steps as Example 2, except that the raw materials of the aluminum alloy in Comparative Example 2 include Al-Zn master alloy, Al-Mg master alloy, Al-Cu master alloy, Al-Mn master alloy, Al-Ni master alloy and pure Al ingot. The raw materials of the aluminum alloy in Comparative Example 3 include Al-Zn master alloy, Al-Mg master alloy, Al-Cu master alloy, Al-Mn master alloy, Al-B master alloy and pure Al ingot. The raw materials of the aluminum alloy in Comparative Example 4 include Al-Zn master alloy, Al-Mg master alloy, Al-Cu master alloy, Al-Mn master alloy, Al-Li master alloy and pure Al ingot.
[0077] The aluminum alloys of Examples 1 to 25 and Comparative Examples 1 to 4 were used to measure the performance parameters of the aluminum alloys. The results are shown in Table 2. The performance parameter test of the aluminum alloy includes: measuring the 0.05 mm 2 The number of second phase particles with a diameter ≥ 8μm in the cross-sectional area is used to determine the room temperature mechanical properties of the aluminum alloy and observe the anode appearance of the aluminum alloy.
[0078] Table 2 Performance parameters of aluminum alloys of Examples 1 to 25 and Comparative Examples 1 to 4
[0079]
[0080] As can be seen from Table 1 and Table 2, the aluminum alloys provided in Examples 1 to 25 have a high-brightness, slightly numbness, or slightly numbness and dumbness anode appearance effects, so that the shell made of the aluminum alloy has a good anode appearance effect, which is beneficial for application in terminal equipment. At the same time, the elastic modulus of the aluminum alloys of Examples 1 to 25 is relatively high, which is beneficial for improving the elastic modulus of the shell made of the aluminum alloy, and has a good application prospect in the terminal equipment. The embodiments of the present application are carried out through a large number of experiments, and the experimental results show that by controlling 4.0%≤Zn≤6.5%, 1.0%≤Mg≤2.8%, 0.1%≤Cu≤4.5%, 0<Mn≤0.6%, 0≤X<6%, 78.2%≤Al≤94.9%, and the total content of inevitable impurity elements in the aluminum alloy is ≤1.0%, the obtained aluminum alloy has a good anode appearance effect and can also have a high elastic modulus.
[0081] Among them, compared with the aluminum alloys without adding X element in Examples 1 to 3, the aluminum alloys in Examples 4 to 25 all added X element, and the elastic modulus of the obtained aluminum alloys was higher than the elastic modulus of the aluminum alloys in Examples 1 to 3, and the lowest elastic modulus could reach 79 GPa. The experimental results show that by adding X element to the aluminum alloy, the elastic modulus of the aluminum alloy can be improved.
[0082] By comparing Comparative Examples 2 to 4 and Examples 4 to 14, although the aluminum alloys in Comparative Examples 2 to 4 have added X element, the addition amount of X element is as high as 6.0%, and the obtained aluminum alloy presents a numb and dull anode appearance effect. The experimental results show that although adding X element is beneficial to improving the elastic modulus of the aluminum alloy, too much X element is not conducive to the aluminum alloy presenting a bright anode appearance effect. In some embodiments, the content of X element in the aluminum alloy is: 0≤X<6%.
[0083] In addition, by comparing Comparative Example 1 with Examples 1 to 3, in the aluminum alloy of Comparative Example 1, the addition amount of the Zn element is as high as 7.0%, exceeding 6.5%, the addition amount of the Mg element is as high as 3.0%, exceeding 2.8%, and the addition amount of the Mn element is as high as 0.8%, exceeding 0.6%. The obtained aluminum alloy presents a numb and dull anode appearance effect. The experimental results show that excessive Zn, Mg and Mn are not conducive to the aluminum alloy presenting a bright anode appearance effect.
[0084] By comparing Examples 15 to 17, Examples 18 to 20, or Examples 2, 1 to 23, by increasing the Cu content in the aluminum alloy, the elastic modulus of the aluminum alloy is gradually increased, the yield strength and tensile strength are gradually increased, and the elongation is gradually increased, showing better toughness. At the same time, by comparing Examples 4 to 6, Examples 7 to 9, or Examples 10 to 12, by increasing the content of the X element in the aluminum alloy, the elastic modulus of the aluminum alloy is gradually increased, and the yield strength and tensile strength are gradually increased. The embodiments of the present application have been verified through a large number of experiments, and controlling the aluminum alloy to 0.2% ≤ Cu ≤ 3.0%, 1.0% ≤ X ≤ 5.5% can ensure that the aluminum alloy has an excellent elastic modulus, as well as a higher yield strength and tensile strength, and the aluminum alloy exhibits toughness. Furthermore, controlling the aluminum alloy to 0.5%≤Cu≤2.0%, 1.0%≤X≤2.0% can ensure that the aluminum alloy has excellent elastic modulus, as well as higher yield strength and tensile strength. While the aluminum alloy exhibits strong toughness, it can also ensure that the aluminum alloy has a bright anode appearance.
[0085] By comparing Examples 4 to 6 with Examples 15 to 17, when the X element added to the aluminum alloy is Ni, the anode appearance effect, elastic modulus, yield strength, tensile strength and elongation of the aluminum alloy can be adjusted by adjusting the mass ratio of Cu to Ni. The embodiments of the present application have been verified through a large number of experiments that the mass ratio of Cu to Ni is controlled to be: Cu: Ni = (0.5 to 2.0): (1.0 to 2.0), which can ensure that the aluminum alloy can obtain excellent elastic modulus, as well as good yield strength, tensile strength and elongation, and the aluminum alloy exhibits toughness, and the aluminum alloy can also obtain a bright anode appearance effect.
[0086] By comparing Examples 7 to 9 with Examples 18 to 20, when the X element added to the aluminum alloy is the B element, the anode appearance effect, elastic modulus, yield strength, tensile strength and elongation of the aluminum alloy can be adjusted by adjusting the mass ratio of Cu to B elements. The embodiments of the present application have been verified through a large number of experiments that the mass ratio of Cu to B elements is controlled to be: Cu: B = (0.5 to 2.0): (1.0 to 2.0), which can ensure that the aluminum alloy can obtain excellent elastic modulus, as well as good yield strength, tensile strength and elongation, and the aluminum alloy exhibits toughness, and the aluminum alloy can also obtain a bright anode appearance effect.
[0087] By comparing Examples 10 to 12 and Examples 21 to 23, when the X element added to the aluminum alloy is Li, the anode appearance effect, elastic modulus, yield strength, tensile strength and elongation of the aluminum alloy can be adjusted by adjusting the mass ratio of Cu to Li. The embodiments of the present application have been verified through a large number of experiments that the mass ratio of Cu to Li is controlled to be: Cu: Li = (0.5 to 2.0): (1.0 to 2.0), which can ensure that the aluminum alloy can obtain excellent elastic modulus, as well as good yield strength, tensile strength and elongation, and the aluminum alloy exhibits strong toughness, and the aluminum alloy can also obtain a bright anode appearance effect.
[0088] By comparing Examples 13 to 14 with Examples 24 to 25, when the X element added to the aluminum alloy is Ni, B and Li, by adjusting the mass ratio of Cu to Ni, B and Li, the anode appearance effect, elastic modulus, yield strength, tensile strength and elongation of the aluminum alloy can be adjusted. The embodiments of the present application have been verified by a large number of experiments, and the mass ratio of Cu to Ni, B and Ni is controlled to be: Cu: Ni: B: Li = (0.5 to 2.0): (0.6 to 1.2): (0.2 to 0.4): (0.4 to 0.7), which can ensure that the aluminum alloy can obtain excellent elastic modulus, as well as good yield strength, tensile strength and elongation, and the aluminum alloy exhibits toughness, and the aluminum alloy can also obtain a bright anode appearance effect.
[0089] In addition, by comparing Comparative Examples 2 to 4 with Examples 1 to 25, in the cross section of the aluminum alloy of Comparative Examples 2 to 4, the thickness of 0.05 mm 2 In the cross-sectional area, the number of second phase particles with a diameter of ≥8 μm is greater than 35, and the obtained aluminum alloy presents a numb and dull anode appearance effect, which is a poor anode appearance effect. In the cross-sectional area of the aluminum alloys of Examples 6, 9, 12, 17, 20 and 23, 0.05 mm 2In the cross-sectional area, the number of second phase particles with a diameter of ≥10 μm is greater than 36 and less than or equal to 36, and the obtained aluminum alloy presents a slightly numb or slightly numb and dull anode appearance effect, and the anode appearance effect of the aluminum alloy is relatively poor. 2 The number of second phase particles with a diameter of ≥10 μm in the cross-sectional area is ≤30, and the obtained aluminum alloys all present a bright anode appearance. 2 Within the cross-sectional area of the aluminum alloy, the number of second phase particles with a diameter ≥8μm is ≤30, which can ensure that the second phase particles are completely dissolved during the anodizing process of the aluminum alloy and does not affect the bright anode appearance of the aluminum alloy.
[0090] What is disclosed above is only a preferred embodiment of the present application, and it certainly cannot be used to limit the scope of rights of the present application. Ordinary technicians in this field can understand that all or part of the processes of implementing the above embodiments and equivalent changes made according to the claims of the present application are still within the scope covered by the present application.
Claims
1. An aluminum alloy, characterized in that: Calculated by the mass of the aluminum alloy, the components of the aluminum alloy include: 4.0%≤Zn≤6.5%, 1.0%≤Mg≤2.8%, 0.1%≤Cu≤4.5%, 0<Mn≤0.6%, 0≤X<6%, 78.2%≤Al≤94.9%, and the total content of inevitable impurity elements ≤1.0%, wherein the X element is selected from at least one of the Ni element, the B element, and the Li element.
2. The aluminum alloy according to claim 1, characterized in that X is a Ni element, and the mass ratio of the Cu to the Ni element is: Cu:Ni=(0.5-2.0):(1.0-2.0).
3. The aluminum alloy according to claim 1, characterized in that X is the B element, and the mass ratio of the Cu to the B element is: Cu:B=(0.5-2.0):(1.0-2.0).
4. The aluminum alloy according to claim 1, characterized in that X is a Li element, and the mass ratio of the Cu to the Li element is: Cu:Li=(0.5-2.0):(1.0-2.0).
5. The aluminum alloy according to claim 1, characterized in that X represents Ni element, B element and Li element, and the mass ratio of Cu to the Ni element, the B element and the Ni element is: Cu:Ni:B:Li=(0.5-2.0):(0.6-1.2):(0.2-0.4):(0.4-0.7).
6. The aluminum alloy according to any one of claims 1 to 5, characterized in that: The aluminum alloy includes an Al matrix and second phase particles dispersed in the Al matrix, the Al matrix is formed of Al element, and the second phase particles are formed of at least two elements selected from the group consisting of Al element, Mg element, Zn element, Cu element, Mn element and X element.
7. The aluminum alloy according to claim 6, characterized in that In the cross section of the aluminum alloy, within 0.05mm 2 Within the cross-sectional area, the number of second phase particles with a diameter ≥ 8 μm is ≤ 30.
8. The aluminum alloy according to any one of claims 1 to 5, characterized in that: The unavoidable impurity elements include at least one of Ti, Cr and Fe.
9. The aluminum alloy according to any one of claims 1 to 5, characterized in that: 0.2%≤Cu≤3.0%, 1.0%≤X≤5.5%.
10. The aluminum alloy according to claim 9, characterized in that 0.5%≤Cu≤2.0%, 1.0%≤X≤2.0%.
11. A housing, characterized in that: The shell is made of the aluminum alloy according to any one of claims 1 to 10.
12. A terminal device, characterized in that: It comprises a display screen and a shell as claimed in claim 11, wherein the display screen is mounted on the shell.
13. The terminal device according to claim 12, characterized in that: The terminal device is a mobile phone, and the shell is a middle frame of the mobile phone; or, the terminal device is a tablet computer, and the shell is a middle frame of the tablet computer; or, the terminal device is a computer, and the shell is a shell of the computer.